1974
DOI: 10.1007/bf00423039
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood flow and metabolic control in juvenile diabetes

Abstract: Peripheral blood flow was measured during periods of good and poor metabolic control in juvenile diabetics with less than five years duration of the disease. Previously insulin treated patients, in whom the insulin was withdrawn for a few days, showed elevated blood flow in muscular, adipose and cutaneous tissue, whereas a group of newly diagnosed diabetics before treatment showed elevated blood flow in adipose and cutaneous tissue only. In good metabolic control the diabetics had normal values of both muscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 12 publications
(12 reference statements)
4
23
0
Order By: Relevance
“…Recent evidence indicates that there are marked abnormalities of blood flow in such legs, suggesting increased velocity of flow and raising the possibility of arterio-venous shunting [27,28]. Forearm blood flow has been shown to be increased in juvenile diabetic patients, this increase being more marked at times of poor metabolic control [29].…”
Section: Blood Flow Abnormalitiesmentioning
confidence: 99%
“…Recent evidence indicates that there are marked abnormalities of blood flow in such legs, suggesting increased velocity of flow and raising the possibility of arterio-venous shunting [27,28]. Forearm blood flow has been shown to be increased in juvenile diabetic patients, this increase being more marked at times of poor metabolic control [29].…”
Section: Blood Flow Abnormalitiesmentioning
confidence: 99%
“…Despite this apparently adequate blood supply these patients sometimes develop non-healing foot ulcers. In agreement with these observations several studies have shown that diabetic patients have an increased blood flow in the extremities [22][23][24], and also an increase of the total skin microcircuIation [25,26]. Peripheral neuropathy, in combination with repeated mechanical stress, is considered the main reason why chronic foot ulcers develop in skin areas with an increased or normal blood flow, but another contributing factor may be a maldistribution of blood between the nutritional capillaries and the deeper subpapillary vessels.…”
Section: Discussionmentioning
confidence: 54%
“…Long-term hyperglycaemia causes endothelial and metabolic disturbances leading to an elevated blood circulation, capillary hypertension and increased vascular leakage [24,36,37,26,38], which may progress to irreversible structural changes [39], such as a thickening of the capillary basement membrane [40]. An increased capillary blood pressure, which has been demonstrated in both the toe and finger nailfolds of diabetic patients [26,38], may be a consequence of an opening of arteriovenous shunt vessels with a transformation of the arteriolar pressure out into the subpapillary venular plexus, resulting in a decreased arteriovenous pressure difference.…”
Section: Discussionmentioning
confidence: 99%
“…It may be suggested that it is in connection with the increased circulatory demands of the periphery and there fore the increased blood flow in the peripheral tissues [35] and kidney [36]. The other reason is probably the domi nant sympathetic tone [14].…”
Section: Discussionmentioning
confidence: 99%